Analytic self-gravitating 4-Baryons, traversable NUT-AdS wormholes, flat space-time multi-Skyrmions at finite volume and a novel transition in the SU(3)-Skyrme model - E. Ayón-Beato; F. Canfora; M. Lagos; J. Oliva; A. Vera (European Physical Journal C: Particles and Fields, 2020)
Abstract We construct the first analytic self-gravitating Skyrmions with higher Baryon charge in four dimensions for the SU(3)-Skyrme–Einstein-$$Λ $$ Λ theory by combining the generalized hedgehog ansatz with the approach developed by Balachandran et al. to describe the first (numerical) example of a non-embedded solution. These are genuine SU(3) analytic solutions instead of trivial embeddings of SU(2) into SU(3) and its geometry is that of a Bianchi IX Universe. The Skyrme ansatz is chosen in such a way that the Skyrme field equations are identically satisfied in the sector with Baryon charge 4. The field equations reduce to a dynamical system for the three Bianchi IX scale factors. Particular solutions are explicitly analyzed. Traversable wormholes with NUT-AdS asymptotics supported by a topologically non-trivial SU(3)-sigma soliton are also constructed. The self-gravitating solutions admit also a suitable flat limit giving rise to Skyrmions of charge 4 confined in a box of finite volume maintaining the integrability of the SU(3) Skyrme field equations. This formalism discloses a novel transition at finite Baryon density arising from the competition between embedded and non-embedded solutions in which the non-embedded solutions prevail at high density while are suppressed at low densities.